Clinical Performance of Ceramic Laminate Veneers Made with Celtra Press and IPS E. Max Press Ceramic (Randomized Controlled Clinical Trial) - Shafeq Aqlan; Lamia Kheiralla; Gihan El-Naggar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objective: To assess the clinical performance (color matching and stability, fracture, marginal adaptation, patient satisfaction, and sensitivity) of laminate veneers constructed from Celtra press ceramic and IPS e.max press ceramic with incisal wrap design (split-mouth design).Methodology: Thirty-four ceramic laminate veneers were fabricated for maxillary anterior teeth in six patients. The veneers were randomly divided into two groups based on their material. Group I (the control group) was constructed from IPS e.max press veneers, and Group II (the intervention group) was constructed from Celtra press veneers. The follow-up sessions were performed after 24 hours of cementation (the baseline), then every three months for up to a year for each patient, using a dental probe and operator vision to assess color matching, fracture, and sensitivity in accordance with USPHS criteria. A spectrophotometer (Vita EasyShade®V) was also used to assess the color stability of the restoration.  Patients’ satisfaction was also evaluated using a questionnaire chart.Results: An insignificant difference in both groups was revealed, considering color matching, color stability, fractures, marginal adaptation, and sensitivity at all follow-up intervals. While patients' satisfaction results showed a statistically significant difference in some evaluated factors, there wasn’t a clinically significant difference.Conclusion: After one year of follow-up, both Celtra press laminate veneers and IPS e.max press laminate veneers showed successful clinical performance in anterior teeth requiring conservative labial laminate veneers with incisal wrap design in terms of color matching and color stability, fracture, marginal adaptation, sensitivity, and patient satisfaction.